HUBUNGAN KADAR HEMOGLOBIN DENGAN PRESTASI BELAJAR PADA REMAJA PUTRI DI SMP NEGERI 2 SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Rummy Islami Zalni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Hemoglobin is a complex protein comprise of globin protein and pigmen heme ( contains of iron) that bulk large in oxygen transportation. It said that at condition where low hemoglobin contents power concertation in learning down seen. Evidence that available showed annoyance at psikomotor development and intelektual ability and change behavior after occur anemia defisiensi iron. Girls adolescent more susceptible anemia because the girl adolescent in period development that needed nutrient more higher included iron. The purposed of this research was to know correlation hemoglobin contents with study achievement of girl adolescent at SMP Negeri 2 Singingi Hilir. This research did at SMP Negeri 2 Singingi Hilir at year 2014 with population as many 103 students in class 1 and 2 with the sample 51 respondents. The research design used descriptif correlation quantitatif. The instrument used checlist sheet and check HB digital touch GCHB. The result of this research showed that good adolescent achiement as many 26 students (51 %), that enough achievement as many 25 students (49 %). Students are included in the category of anemia as 42 students (82,4 %), and are included in the category of anemia is not as much 9 students (17,6 %). Based on the result test bivariat got there is no significant correlation between hemoglobin contents with study achievement of girl adolescent at SMP Negeri 2 Singingi Hilir (p value = 0,76 > α 0,05). Suggestion for girl adolescent to consume nutriment and higher iron to help development and prevent anemia.